The Effectiveness of Salary and Intensive Pay in Improving HR Performance at J&T Express Ponorogo Branch Office - Sari, Dita Harnika; Hidayat, Rahmat; Kusworo, Ahmad Dzulfikri Budi (Indonesian Journal Publisher, 2024)
J&T Express Ponorogo is one of the J&T Express branch offices located in the Ponorogo region, East Java. J&T Express Ponorogo is a branch office of an expedition company whose main field is in the service and delivery of retail goods. It is fundamental that in every operation of J&T Express Ponorogo it is required to apply excellent service in all matters related to the shipments made. Of course, the role of human resources is very instrumental in providing excellent service for the satisfaction of existing customers. It can even be said that the progress of organizations and companies can be greatly influenced by the human resources that exist as the front guard in providing services. In this case, it is likely that it will be closely related to the salaries and incentives received by existing human resources. The problem that arises in this study is the decrease and increase in the level of implementation of human resource performance which depends on the provision of salaries and incentives for existing human resources. The formulation of the problems raised in this study is how the effectiveness of providing salaries and incentives in improving HR performance and what factors determine the amount of salaries and incentives received by HR at the J&T Express Ponorogo branch office. The research method applied is direct research using a qualitative descriptive approach to the sample or research target, namely HR who play a role in each office operation for each position at the J&T Express Ponorogo branch office. For data collection itself is done through direct observation, interviews and study of related documents. Conclusion The effectiveness of providing salaries and incentives on HR performance at the J&T Express Ponorogo branch office is considered to be in a very effective category. So that in this case with high salaries and incentives it is very effective to make HR more enthusiastic and always provide the best performance